1986
DOI: 10.1111/j.1476-5381.1986.tb10255.x
|View full text |Cite
|
Sign up to set email alerts
|

α2‐Adrenoceptor‐mediated contractile response to catecholamines in smooth muscle strips isolated from rainbow trout stomach (Salmo gairdneri)

Abstract: 1The type of adrenoceptor involved in the contractile response to catecholamines in smooth muscle strips isolated from rainbow trout stomach was determined.2 Noradrenaline (10 nM-10 ptM) and adrenaline (10 nM-3 pM) caused non-sustained contractions which were markedly decreased by phentolamine (5.4 pM) but not by carteolol (5 PM). Phenylephrine(1 jiM -1 mM) was less effective in causing muscle contraction and methoxamine produced no contraction. Clonidine (100 nM-300JM) caused no mechanical response but inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…The results of the present experiments confirm the previous observations that TMS causes tetrodotoxin-sensitive frequency-dependent contractions of the rainbow trout stomach strips (Holmgren & Nilsson, 1981;Kitazawa et al, 1986). Atropine significantly decreased the response to low frequency stimulation, but did not decrease that to highfrequency stimulation, and, therefore, it was suggested that low frequency stimulation mainly excited cholinergic excitatory nerves and high frequency stimulation excited non-cholinergic excitatory nerves.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of the present experiments confirm the previous observations that TMS causes tetrodotoxin-sensitive frequency-dependent contractions of the rainbow trout stomach strips (Holmgren & Nilsson, 1981;Kitazawa et al, 1986). Atropine significantly decreased the response to low frequency stimulation, but did not decrease that to highfrequency stimulation, and, therefore, it was suggested that low frequency stimulation mainly excited cholinergic excitatory nerves and high frequency stimulation excited non-cholinergic excitatory nerves.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, histamine did not cause any mechanical response at a fairly high concentration (100pM) and pyrilamine had no inhibitory effect on the response to TMS (Table 1) (n = 5). This response to noradrenaline was selectively decreased by phentolamine (5.4pM) and yohimbine (1 M), but not by prazosin (1 pM), indicating that the excitatory response to noradrenaline was mediated by a-adrenoceptors, as previously observed (Kitazawa et al, 1986). The a-adrenoceptor antagonist, phentolamine (5.4pM), had no inhibitory effect on the atropine-resistant contraction caused by TMS (Table 1).…”
Section: Extraction and Bioassaysupporting
confidence: 73%
See 2 more Smart Citations
“…The contractile response to noradrenaline and adrenaline in this species involves both a direct action on smooth muscle and an indirect action through a non-cholinergic excitatory nerve (Kitazawa, 1986). Enteric neurons may release acetylcholine, 5-hydroxytryptamine and neuropeptides in various combinations (Holmgren and Nilsson, 1991;Jensen and Holmgren, 1993 (Holmgren and Nilsson, 1976;Winberg et ai., 1981).…”
Section: H Malabaricus Is a Moderately Voracius Carnivorous Speciesmentioning
confidence: 99%